An active charge –exchange q measurements in ITER based upon the diagnostic hydrogen beam - Medvedev, A.A.; Strelkov, V.S. (Вопросы атомной науки и техники, 2006)
The active charge exchange technique based upon Secondary Charge Exchange effect (SCX) is proposed for safety factor measurements in ITER. The performed numerical modeling shows that measurements of the magnetic pitch angle are possible up to the plasma center with radial resolution of 5 cm and integration time of about 10 ms. A systematic inaccuracy amounts several milliradians. An important advantage of SCX technique is the possibility of direct pitch angle measurements.